Substituent Electrophilicities in the Nmr Spectra of Barbituric Derivatives - Caroli-Rezende, M; Almodovar-Fajardo, I (2012)
Comparison of the 1H and 13 C NMR spectra of a series of substituted 5-benzylidene-N,N?-dimethylbarbituric acids (1) revealed chemical-shift variations of different centers that correlated with the theoretical electrophilicities or with the substituent electrophilic constant ? ?, in an example of the usefulness of these DFT-based indices. Copyright © 2012 John Wiley & Sons, Ltd.